To Study Job-related Stress on Employee Performance between Private and Public Sector Banks - LIPINRAJ K Kattilayil house; Dr. S. Madasamy (Journal of Advanced Zoology, 2024)
This research abstract focuses on investigating the correlation between job-related stress and employee performance within both private and public sector banks. The study aims to discern potential differences in stress levels and performance outcomes between these two sectors. By employing comparative analysis, the research seeks to shed light on how varying organizational structures and work environments influence the relationship between job-related stress and employee performance. Understanding these dynamics can offer valuable insights for policymakers and organizational leaders to develop effective strategies for enhancing employee well-being and productivity in the banking industry. The research included a total 60 participants from both public and private banks located in Thrissur, Kerala. Data collection involved using the Census method to gather responses from individual employees, and statistical analyses such as correlation, and independent t-sample tests were conducted using SPSS version 26.0 to examine the data.